Effect of Positive end expiratory pressure during one-lung ventilation on hemodynamics in thoracic surgeries in adult patients - Mohammed Aly Mubarak*; Ahmed Fathy Abdel-Latif; Mohamed Abdel-Bary; Gad Sayed Gad (SVU - International Journal of Medical Sciences, 2020)
Background: One-lung ventilation (OLV) is a common practice during thoracic surgery involving pulmonary resection to facilitate surgical exposure. For long time, arterial hypoxemia during OLV was is the most important problem for the anesthesiologist. At present, there is increasing concern about the effects of ventilator settings on acute lung injury. Objectives: The aim of this study is to compare the effect of different levels of Positive end expiratory pressure (PEEP) on hemodynamics in thoracic surgeries in adult patients. Patients and Methods: This is a prospective study that included 60 adult patients undergoing elective thoracic procedures requiring one-lung ventilation through a posterio-lateral thoracotomy at cardio-thoracic surgery department in Qena university hospital “between October 2017 to April 2019”, the Sixty patients were assigned to three groups: group I received no PEEP (n = 20),group II received a PEEP (5 cmH2O) (n = 20),and group III received a PEEP (10 cmH2O) (n = 20). Patient hemodynamics, pulmonary mechanics, and arterial blood gases were measured just after OLV(T1) and 20 (T2), 40 (T3), and 60 min(T4) after OLV. Results: All cases were completed successfully. The heart rate and mean arterial blood pressure showed no significant changes between all groups. Conclusion: During OLV, mechanical ventilation with PEEP 0, 5 or 10 cmH2O has no effect on hemodynamics in thoracic surgeries in adult patients.